Duke Vincentio: A Paragon of a Christian Prince or a Self-Centered Manipulator? - Tagong, Kanchit (Asian Health, Science and Technology Reports, 2011)
Many critics have asserted that Duke Vincentio, in Shakespeare’s Measure for Measure, is a good Christian prince-a man who is full of love, beneficence, and benevolence for other people. However, upon a closer examination, the prince is a hypocritical, selfcentered, and manipulative person. What he has done is primarily to maintain his own image and reputation.